A survey on education in cariology for undergraduate dental students in Europe - Schulte, Andreas G.; Buchalla, W.; Huysmans, M.-C. D. N. J. M.; Amaechi, B. T.; Sampaio, F.; Vougiouklakis, G.; Pitts, N. B. (European journal of dental education, 2011)
The aim of the survey was to collect relevant information about education in cariology for dental undergraduate students in Europe. The ORCA/ADEE cariology curriculum group prepared a questionnaire that was mailed in 2009 to 179 European dental schools. One hundred and twenty-three dental schools (72%) from 32 countries completed and returned the questionnaires. In most of these schools, education in cariology is delivered by at least two different units. The units mainly involved are Paediatric Dentistry, Conservative Dentistry, Restorative Dentistry or Operative Dentistry. Theoretical education in cariology is delivered by practically all responding dental schools, and in 96% of these schools, it starts within the first 3 years. Pre-clinical exercises are offered by 98% of the schools starting mainly in the third or fourth year. In 97% of the schools, clinical exercises are carried out, and this occurs mainly in the fourth and fifth year. In nearly all dental schools (88%), education in cariology comprises not only caries but also dental erosion and non-erosive wear. The vast majority of the responding dental schools (89%) supported the idea of developing a European Core Curriculum in Cariology.
Gesehen am 27.10.2022